Solve for x, y

x = \frac{100}{23} = 4\frac{8}{23} \approx 4.347826087<br/>y = \frac{213700}{23} = 9291\frac{7}{23} \approx 9291.304347826

$x=23100 =4238 ≈4.347826087$

$y=23213700 =9291237 ≈9291.304347826$

$y=23213700 =9291237 ≈9291.304347826$

Graph

Still have questions?

Ask a tutor instantly - for free

Share

Copy

Copied to clipboard

\frac{77}{100}y+2137-y=0

Consider the second equation. Subtract y from both sides.

-\frac{23}{100}y+2137=0

Combine \frac{77}{100}y and -y to get -\frac{23}{100}y.

-\frac{23}{100}y=-2137

Subtract 2137 from both sides. Anything subtracted from zero gives its negation.

y=-2137\left(-\frac{100}{23}\right)

Multiply both sides by -\frac{100}{23}\approx -4.347826087, the reciprocal of -\frac{23}{100}=-0.23.

y=\frac{213700}{23}

Multiply -2137 and -\frac{100}{23}\approx -4.347826087 to get \frac{213700}{23}\approx 9291.304347826.

2137x=\frac{213700}{23}

Consider the first equation. Insert the known values of variables into the equation.

x=\frac{\frac{213700}{23}}{2137}

Divide both sides by 2137.

x=\frac{213700}{23\times 2137}

Express \frac{\frac{213700}{23}}{2137}\approx 4.347826087 as a single fraction.

x=\frac{213700}{49151}

Multiply 23 and 2137 to get 49151.

x=\frac{100}{23}

Reduce the fraction \frac{213700}{49151}\approx 4.347826087 to lowest terms by extracting and canceling out 2137.

x=\frac{100}{23} y=\frac{213700}{23}

The system is now solved.

Examples

Quadratic equation

{ x } ^ { 2 } - 4 x - 5 = 0

$x_{2}−4x−5=0$

Trigonometry

4 \sin \theta \cos \theta = 2 \sin \theta

$4sinθcosθ=2sinθ$

Linear equation

y = 3x + 4

$y=3x+4$

Arithmetic

699 * 533

$699∗533$

Matrix

\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { - 1 } & { 1 } & { 5 } \end{array} \right]

$[25 34 ][2−1 01 35 ]$

Simultaneous equation

\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.

${8x+2y=467x+3y=47 $

Differentiation

\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }

$dxd (x−5)(3x_{2}−2) $

Integration

\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x

$∫_{0}xe_{−x_{2}}dx$

Limits

\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}

$x→−3lim x_{2}+2x−3x_{2}−9 $